2021
DOI: 10.5194/se-12-1111-2021
|View full text |Cite
|
Sign up to set email alerts
|

Reply to Norini and Groppelli's comment on “Estimating the depth and evolution of intrusions at resurgent calderas: Los Humeros (Mexico)” by Urbani et al. (2020)

Abstract: Abstract. Structural studies in active caldera systems are widely used in geothermal exploration to reconstruct volcanological conceptual models. Active calderas are difficult settings to perform such studies mostly because of the highly dynamic environment, dominated by fast accumulation of primary and secondary volcanic deposits, the variable and transient rheology of the shallow volcanic pile, and the continuous feedbacks between faulting, secondary porosity creation, and geothermal fluid circulation, alter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 47 publications
(136 reference statements)
3
4
0
Order By: Relevance
“…However, high-temperature alteration minerals, such as garnet, diopside, and wollastonite, were also observed at shallower depth levels as shown in fracture fillings of sample H38-4 (1950 m) in the central to northern zones of the geothermal field (also referred to as the central collapse area). This observation is well in line with findings from (i) Martıńez-Serrano (2002), who defined the beginning of a skarn zone at about 1800 m depth in the central collapse area, (ii) Jentsch et al (2020), who reported the highest temperature anomalies at Loma Blanca within the central collapse area, as well as (iii) Urbani et al (2021), who discussed existing borehole-temperature profiles in the same area. However, our findings show that high-temperature secondary mineral assemblages are not limited to the central collapse area as previously described in Prol-Ledesma and Browne (1989).…”
Section: Petrography and Hydrothermal Alterationsupporting
confidence: 89%
See 4 more Smart Citations
“…However, high-temperature alteration minerals, such as garnet, diopside, and wollastonite, were also observed at shallower depth levels as shown in fracture fillings of sample H38-4 (1950 m) in the central to northern zones of the geothermal field (also referred to as the central collapse area). This observation is well in line with findings from (i) Martıńez-Serrano (2002), who defined the beginning of a skarn zone at about 1800 m depth in the central collapse area, (ii) Jentsch et al (2020), who reported the highest temperature anomalies at Loma Blanca within the central collapse area, as well as (iii) Urbani et al (2021), who discussed existing borehole-temperature profiles in the same area. However, our findings show that high-temperature secondary mineral assemblages are not limited to the central collapse area as previously described in Prol-Ledesma and Browne (1989).…”
Section: Petrography and Hydrothermal Alterationsupporting
confidence: 89%
“…We interpret silicification at shallower depth levels within the propylitic alteration zone as well as the local occurrence of high-temperature minerals at different depth levels as possible evidence of shallow intrusions, in agreement with the shallowest geometry of the Los Humeros post-caldera stage magmatic plumbing system (Lucci et al 2020) and with the results from field-constrained analog modeling proposed by Urbani et al (2020Urbani et al ( , 2021. Shallow cryptodomes (e.g., Urbani et al 2020Urbani et al , 2021 and/or magma pockets (Lucci et al 2020) could be also responsible for thermal metamorphism in limestones and lavas that locally underwent transformation to marble, hornfels, and skarn, respectively. Furthermore, the occurrence of low and high-temperature alteration minerals at the same depth or even within one sample (Martıńez-Serrano 2002;Prol-Ledesma 1998), plus the high variability of alteration facies and intensity in the upper section of the pre-caldera group, points to the possibility of several heterogeneous heat sources.…”
Section: Petrography and Hydrothermal Alterationsupporting
confidence: 86%
See 3 more Smart Citations